Determinants of Sustainable Tourism Villages in Bali: The Roles of Digital Marketing, Corporate Social Responsibility, and Tri Hita Karana - Wayan Ardani (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2026)
The development of sustainable tourism villages has become a strategic approach to promoting local economic growth while preserving environmental and cultural resources. However, empirical studies integrating institutional, social, environmental, cultural, and technological factors within a single framework remain limited. This study aims to analyze the determinants of sustainable tourism village development in Bali by examining the effects of government support, community empowerment, and green marketing, both directly and indirectly through Tri Hita Karana (THK)-based Corporate Social Responsibility (CSR) and digital marketing. A mixed-methods approach with an exploratory sequential design was employed. The qualitative phase involved Focus Group Discussions (FGDs) with tourism stakeholders to identify key constructs and develop the research instrument. The quantitative phase was conducted through a survey of 185 tourism village stakeholders in Bali and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that government support, community empowerment, green marketing, THK-based CSR, and digital marketing significantly influence sustainable tourism. Among these factors, THK-based CSR emerged as the strongest determinant of sustainable tourism, while green marketing demonstrated the strongest effect on digital marketing. Furthermore, THK-based CSR significantly mediates the effects of government support and community empowerment, whereas digital marketing mediates the effects of community empowerment and green marketing on sustainable tourism. These findings highlight the importance of integrating local cultural values, environmental responsibility, and digital transformation into tourism village management. The study contributes to sustainable tourism literature by positioning Tri Hita Karana as a cultural foundation for CSR and digital marketing as a strategic mechanism for enhancing tourism village sustainability and competitiveness.